Evaluation The Post-Processing Kinematic Method In The Global Navigation Satellite Systems (GNSS) In Terms Of Accuracy And The Efficiency Of The Used Processing Program - حبيب غيث; ندى محفوض; فايز ديب (Latakia University Journal -Engineering Sciences Series, 2022)
Global Navigation Satellite Systems (GNSS) is of importance in the work of topographic and cadastral surveys, geographic information systems and geological mapping, so the accuracy of GNSS must evaluate. Therefore, the main objective of this research is to evaluate the accuracy of one of the kinematic methods in GNSS, which is called the Post-Processing Kinematic (PPK) method, according to the difference in each of the field observation parameters (obstructions, time, cut-off angle and initialization point), number of observation periods as well as the effect of the processing program used, that is by comparing the coordinates (X,Y,Z) resulting from each case with the coordinates resulting from observation by the traditional method, where the results were tabulated and represented in graphs. The results proved the possibility of using the PPK method in the works of medium-accuracy surveying works and cadastral surveying.